EFFICACY OF FUNGAL PHYTASE ON APPARENT ILEAL DIGESTIBILITY OF NUTRIENTS IN BROILER CHICKEN - M, Manobhavan; Sridhar, Manpal; Ajith, Sreeja; Shet, Divya; D.T., Pal; N.K.S., Gowda; A.V., Elangovan (Indian Journal of Animal Nutrition, 2020)
This experiment was conducted to assess efficacy of phytase of fungal (Aspergillus foetidis)-origin on apparent ileal digestibility of nutrients in broiler chicken fed with a maize-soybean based diet. A feeding trial consisted of 126 chicks, divided into three dietary treatments with six replicates having seven chicks in each following a completely randomized design. Semi purified phytase of Aspergillus foetidis (MTCC 11682) was used for feeding. The dietary treatments consisted of one normal phosphorus (NP) group without any phytase enzyme, two low phosphorus (LP) groups LP500 and LP1000 with supplemented laboratory phytase at 500 and 1000 FTU/kg, respectively. The apparent ileal digestibility coefficient (AIDC) of most amino acids were improved significantly (p